SIGNIFICANT ROLE OF CLINICAL PHARMACISTS IN THE ASSESSMENT OF INAPPROPRIATE MEDICATIONS PRESCRIBED TO THE ELDERLY PATIENTS IN A UNIVERSITY TEACHING HOSPITAL - Umar, Neethu Fathima; Umar, Neethu Fathima (Asian Journal of Pharmaceutical and Clinical Research, 2015)
The elderly people experience a higher incidence of diseases, physical impairment, medication use, and adverse drug effects than younger adults therefore care must be taken while prescribing the drugs in this group. The present study was under taken by the clinical pharmacists of a tertiary care teaching hospital with the aim of assessing the potentially inappropriate medications (PIMs) in the elderly patients by comparing with the American Geriatric Society (AGS) 2012 updated Beers criteria. This clinical tool was developed to improve the care of older adults by reducing their exposure to potentially inappropriate medications .The criteria consist of medications in which the risk out weights the benefits. During the study period of six months a total of 203 patients were enrolled. It includes 121 (59.6%) males and 82 (40.4%) female patients. The mean ages of the patients were 70 years ± 2.480 S.D. The mean medication prescribed per patient was 7.08 ±2.480 S.D. The patients had an average stay of 14.58 days in the hospital with a range of one to three weeks stay .There were 76 (37.4%) inappropriate prescriptions and 127 (62.6%) appropriate prescriptions as per the Beer's criteria. The common inappropriate drugs prescribed included NSAID's (20.19%), Anxiolytics (13.79%), Antidepressants (5.41%), Antihypertensive (3.94%), Antispasmodics (2.65%), Anticonvulsants (1.97%), Sedative and hypnotics (1.47%), Antihistamines (0.98%), Antidiabetics (0.98%), and Antibiotics (0.98%). Polypharmacy and the duration of hospital stay were identified as risk factors for inappropriate medication. The study proved that clinical pharmacist can contribute his skill and knowledge to achieve better therapeutic outcomes in the patients. Key words: Potentially inappropriate medications, Elderly patients, Clinical pharmacist, Beers Criteria